RELATIONSHIP BETWEEN FEEDING AND OVARIAN CYCLE IN SCHIZOTHORAX NIGER HECKEL AND BOTIA BIRDI CHAUDHRY - Malhotra, Y R (Indian Journal of Fisheries, 2011)
Miescher (1897) has shown that salmon go practically without food so long as they are in fresh water, being nourished by the large store of fat deposited when they were in the sea. Carr (1908, 1909) observed high percentages of empty stomachs among specimens of Pleuronectes limanda, Hippoglossus limandoides and Gadus merlangus during the winter months and he attributed this to low temperature. Russel (1914) and Todd (1915) associated the empty stomachs of Pleuronectes platessa with the advent of spawning. Bigelow and Welsh (1924) working on Osmerus mordax, Pomolobus pseudoharengus and Alosa sapidissima stated that the cessation of feeding in fresh waters by these anadromou^ fishes is due to their spawning migrations. Homans and Vladykov (1954) have observefi that the haddock Melanogrammus aegilifinus ceases to take food during the spawning season, but feeds voraciously after termination of the spawning season, trying to regain the weight lost due to spawning.